Utilization of Index Card Match Method in Islamic Learning to Improve Student Learning Outcomes at SD Negeri Anoe Puteh - Nilawati; Marliza (Journal of Indonesian Primary School, 2025)
In the learning process there are many learning methods that can be used by teachers, but not all learning models are suitable for all teaching materials. For this reason, teachers are required to be able to choose a learning model that is relevant to the learning material, one of the learning methods that can be used by teachers in the learning process is the Index Card Match method. The expected objectives of this study are to determine the activities of students and teachers and to determine the improvement in learning outcomes of class II students of Anoe Puteh Elementary School in Islamic Religious Education learning on the material of emulating the noble qualities of Asmaul Husna. This research was conducted using a Classroom Action Research approach, the subjects in this study were class II students of Leukuen Elementary School in the 2022/2023 academic year. This study consists of two cycles, each cycle consists of planning, implementation, observation and reflection. Data collection techniques use observation and test techniques. For data processing using qualitative descriptive analysis techniques. The results of cycle 1 learning activities show that the level of student learning completion is only 63.16% with an average class score of 71.05%, student activity is only 60% and teacher activity is 61.36%. The results show that not all students have scored above the KKM. Therefore, the classroom action research was continued in cycle 2. The level of student learning completion in cycle 2 increased to 84.21%, as well as student activity increased to 85% and teacher activity 86.36% with an average class score of 80. Thus, learning using the Index Card Match method in learning the material of emulating the noble nature of Asmaul Hunsa can be said to be successful. And the author assumes that this research does not need to be continued to cycle 3, because the learning outcomes of cycle 2 have met the Minimum Completion Criteria target that has been set previously.